Attention to context: U.S. and Japanese children’s emotional judgments - Kuwabara, Megumi (2011)
A growing number of studies suggest cultural differences in the attention and evaluation of information in adults (Masuda & Nisbett, 2001; Markus & Kitayama, 1991; Hedden, Ketay, Aron, Markus, & Gabrieli, 2008). One cultural comparison, between Westerners, such as Americans, and Easterners, such as the Japanese, suggest that Westerners typically focus on a central single object in a scene while Easterners often integrate their judgment of the focal object with surrounding contextual cues. There are few studies of whether such cultural differences are evident in children. This study examined 48 monolingual Japanese-speaking children residing in Japan and 48 monolingual English-speaking children residing in the U.S.A. (40 to 60 month-olds) in a task asking children to complete a picture by adding the proper emotional expression to a face. The key variable was the context and shift in context from the preceding trial for the same pictured individual. Japanese children were much more likely to shift their judgments with changes in context whereas children from the United States treated facial expression in a more trait-like manner, maintaining the same expression for the individual across contexts.